Examining trends in gun violence injuries before and during the COVID-19 pandemic across six trauma centers. Issue 1 (10th January 2022) - McGraw, Constance; Jarvis, Stephanie; Carrick, Matthew; Lieser, Mark; Madayag, Robert M; Berg, Gina M; Banton, Kaysie L; Hamilton, David; Bar-Or, David
Abstract : Objectives: The onset of the national stay-at-home orders accompanied by a surge in firearm sales has elevated the concerns of clinicians and public health authorities. The purpose of this study was to examine the impact of the stay-at-home orders among gunshot wound (GSW) trauma admissions. Methods: This was a retrospective cohort study at six level I trauma centers across four states. Patients admitted after the onset of COVID-19 restrictions (March 16, 2020–June 30, 2020) were compared with those admitted during the same period in 2019. We compared (1) rate of patients with GSW and (2) characteristics of patients with GSW, by period using Χ 2 tests or Fisher's exact tests, as appropriate. Results: There were 6996 trauma admissions across the study period; 3707 (53%) in 2019 and 3289 (47%) in 2020. From 2019 to 2020, there was a significant increase in GSW admissions (4% vs. 6%, p=0.001); 4 weeks specifically had significant increases (March 16–March 23: 4%, April 1–April 8: 5%, April 9–April 16: 6%, and May 11–May 18: 5%). Of the 334 GSWs, there were significant increases in patients with mental illness (5% vs. 11%, p=0.03), alcohol use disorder (2% vs. 10%, p=0.003), substance use disorder (11% vs. 25%, p=0.001), and a significant decrease in mortality (14% vs. 7%, p=0.03) in 2020. No other significant differences between time periods were identified. Conclusion: Our data suggest that trauma centers admitted significantly more patients with GSW following the national guidelines, including an increase in those with mental illness and substance use-related disorders. This could be attributable to the stay-at-home orders. Level of evidence: Level III, retrospective study.